Analisis Sistem Manajemen Mutu Iso 9001:2015 Pada Proses Bisnis Dan Pemenuhan Kepuasan Pelanggan Pt Inka Multi Solusi - Adela Aurelia Kinaya Dewi; indah Respati Kusumasari (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The impact of globalisation has caused competition between companies to become more competitiveThe prevailing competition necessitates that numerous companies must demonstrate sustained growth,, this is intended so that companies can continue to face all forms of challenges and competition that exist due to the impact of globalisation. In facing global competition, companies must pay attention to the quality of products produced because the level of consumer awareness of the quality of a product is increasing. For this reason, companies need to obtain international recognition that certifies the conformity of products and company systems to standards. Consistent implementation of this standard is expected to have an impact on customer loyalty. In this study, the main focus lies on the implementation of ISO 9001:2015 Quality Management System and its impact on business processes and customer satisfaction, along with the factors that support or hinder its implementation. The analytical methods used include qualitative approaches, such as observation, documentation, and interviews, as a way to collect data. Data collection was conducted through observation, documentation, and interview techniques with informants selected using purposive sampling method.